A rare variant of knee dislocation - Hussin, Paisal; Mawardi, Maliza; Ab Halim, Ashraf Hakim (CIC Edizioni Internazionali, 2016)
Knee dislocation is a rare injury. It represents less than 0.2% of orthopaedic injuries. This case reports a rare form of knee dislocation caused by the impact of a high-energy trauma. In these cases the appropriate assessment and management is needed to ensure that patient receives the proper treatment.